The Effects of Telework and On-Site Work on Job Performance Mediated by Work Engagement in the Tire Manufacturing Industry: - - Ernawan Dwi Hanartyo; Wahyu Tripurnomo (PT Inovasi Pratama Internasional, 2026)
Changes in work systems require companies to understand how remote work and on-site work arrangements influence employee engagement and performance. This study aims to analyze the effect of telework and on-site work on job performance, with work engagement as a mediating variable among permanent (non-production) employees in the tire manufacturing industry in the Bekasi and Karawang regions. This study adopts a quantitative approach using a saturated (census) sampling technique by distributing questionnaires to 109 permanent employees aged 22–55 years. The data were analyzed using Structural Equation Modeling (SEM). The results indicate that all proposed hypotheses are supported. On-site work is found to have the strongest influence on work engagement, while telework also plays an important role in supporting employee job performance. In addition, both telework and on-site work contribute to the development of work engagement. Furthermore, work engagement plays a crucial role in enhancing job performance and serves as a mediating factor in the relationship between telework, on-site work, and job performance. These findings suggest that work engagement is a key factor in explaining how organizational work arrangements influence employee performance. This study provides practical contributions for manufacturing companies in designing appropriate work system policies by emphasizing work engagement as a strategy to improve employee job performance in a sustainable manner. Future research is recommended to expand the scope of the study across broader regions and different industry sectors, as well as to include additional relevant variables to enrich the understanding of work system management and employee performance.